Price Competition in a Channel Structure with a Common Retailer - Choi, S. Chan (Marketing Science, 1991)
In recent studies of channel competition, it has been found that channel intermediaries reduce the intensity of direct competition between manufacturers. The underlying channel structure in most studies consists of two manufacturers and two retailers each of whom sells only one manufacturer's product exclusively. This paper adds to this growing literature of channel competition by analyzing a channel structure with two competing manufacturers and one intermediary (a common retailer) that sells both manufacturers' products. Unlike some exclusive dealers or retail outlets of a manufacturer, however, a common retailer is often a powerful player in the market. This paper studies three noncooperative games of different power structures between the two manufacturers and the retailer, i.e., two Stackelberg and one Nash games. It is shown that some of the results depend critically on the form of the demand function. With a linear demand function, a manufacturer is better off by maintaining exclusive dealers while a retailer has an incentive to deal with several producers. All channel members as well as consumers are better off when no one dominates the market. The common retailer benefits more than the manufacturers do from a symmetric decrease in the manufacturing cost. As products are less differentiated, all channel members' prices and profits increase: a counterintuitive result. When the demand function is nonlinear, however, an exclusive dealer channel provides higher profits to all than a common retailer channel given a power structure. As products are more differentiated, a manufacturer's profit decreases when a common retailer is used, but increases when an exclusive dealer is used. These results underscore the importance of choosing a correct demand function for a channel decision.